Quantitative Relationship of Thigh Adipose Tissue With Pain, Radiographic Status, and Progression of Knee Osteoarthritis. Issue 4 (April 2015) - Dannhauer, Torben; Ruhdorfer, Anja; Wirth, Wolfgang; Eckstein, Felix
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to explore the relationship of thigh subcutaneous fat (SCF) and intermuscular fat (IMF) content with knee osteoarthritis (KOA) cross-sectionally and longitudinally, using quantitative magnetic resonance imaging. Specifically, we examined relationships with frequent knee pain, various radiographic strata, and structural progression status of KOA. Materials and Methods Subjects who showed between-knee discordance of frequent versus no pain (n = 48), osteophyte versus no radiographic KOA (n = 55), and radiographic joint space narrowing versus no joint space narrowing (n = 44) were selected from the Osteoarthritis Initiative. Knees with structural progression of KOA (n = 23) were compared with knees without progression. Axial thigh magnetic resonance images were used to determine IMF and SCF. Differences between knees and between baseline and 2-year follow-up were examined using paired t tests. Results Women displayed similar amounts of IMF, but twice the SCF of men. Limbs of women with frequently painful knees had statistically significant greater IMF areas (+4.2%; P = 0.05) than contralateral pain-free limbs did. No significant cross-sectional differences were observed between other strata. Men with structural progression appeared to have a greater longitudinal increase in SCF (+13.2%; P < 0.05) than did men without progression (−1.9%), and women with progression appeared to have a greater increase in IMF (+11.6%) than did those without progression (+1.5%). Conclusion In women, painful knees display greater IMF content than do contralateral pain-free knees. Other between-knee comparisons did not reveal a regional association between radiographic KOA and thigh adipose tissue status. Structural progression of KOA may be associated with greater longitudinal increases in SCF in men and greater increases of IMF in women, compared with nonprogressive controls.